Enteric coated HPMC capsules plugged with 5-FU loaded microsponges: a potential approach for treatment of colon cancer - Ankita Gupta; Gaurav Tiwari; Ruchi Tiwari; Rishabh Srivastava; A. K. Rai (Universidade de São Paulo, 2015)
The work was aimed at developing novel enteric coated HPMC capsules (ECHC) plugged with 5 Florouracil (5-FU) loaded Microsponges in combination with calcium pectinate beads. Modified quasi-emulsion solvent diffusion method was used to formulate microsponges based on 32 factorial design and the effects of independent variables (volume of organic solvent and Eudragit RS100 content) on the dependent variables (Particle size, %EE & % CDR) were determined. The optimized microsponges (F4) were characterized by SEM, PXRD, TGA and were plugged along with calcium pectinate beads in HPMC capsules and the HPMC capsules were further coated with enteric polymer Eudragit L 100 (Ed-L100) and/ or Eudrgit S 100 (Ed-S 100) in different proportions. In vitro release study of ECHC was performed in various release media sequentially SGF for 2 h, followed by SIF for the next 6 h and then in SCF (in the presence and absence of pectinase enzyme for further 16 h). Drug release was retarded on coating with EdS-100 in comparison to blend of EdS-100: EdL-100 coating. The percentage of 5-FU released at the end of 24 h from ECHC 3 was 97.83 ± 0.12% in the presence of pectinase whereas in control study it was 40.08 ± 0.02% drug. The optimized formulation was subjected to in vivo Roentgenographic studies in New Zealand white rabbits to analyze the in vivo behavior of the developed colon targeted capsules. Pharmacokinetic studies in New Zealand white rabbits were conducted to determine the extent of systemic exposure provided by the developed formulation in comparison to 5-FU aqueous solutions. Thus, enteric coated HPMC capsules plugged with 5-FU loaded microsponges and calcium pectinate beads proved to be promising dosage form for colon targeted drug delivery to treat colorectal cancer.